Efektifitas Penggunaan Aplikasi Belajar “Ruangguru” terhadap Pemahaman dan Kenyamanan Belajar Ilmu Pengetahuan Alam (IPA) - Meiga Dwi Susanti; M. Anas Thohir (Jurnal Sekolah Dasar, 2023)
21st century education in the form of education that always moves in line with the progress of the times based on changes in the educational paradigm from conventional to modern century education. However, not all educators are ready and able to keep up with the times, so students need to move to achieve real educational goals. The purpose of this study was to determine the understanding and comfort of students' learning when using the "Ruangguru" learning application, especially in class IV the material for animal and plant locomotion. This study uses a descriptive qualitative approach with the aim of describing students' understanding and learning comfort in more detail and depth. The subjects of this study were twelve fourth grade students in two elementary schools in Kediri Regency. The results showed that students felt comfortable and their understanding increased when using the "Ruangguru" learning application in learning the material. The convenience of learning is shown by not being disturbed by students with other online activities and the use of animations that help visualize the picture of the material. Meanwhile, students' understanding is shown by the written test results that are in line with expectations.